Hop domination polynomial of graphs. (18th May 2020) - Mojdeh, D. A.; Emadi, A. S.
Abstract: Let G be a simple graph of order n . The hop domination polynomial of G is the polynomial, where d h ( G, i ) is the number of hop dominating sets of G of size i and γ h ( G ) is the hop domination number of G . In this paper we study d h ( G, i ) of a graph. We classify many families of graphs by studying their hop domination polynomial.